2020
DOI: 10.1007/s11105-020-01213-2
|View full text |Cite
|
Sign up to set email alerts
|

Identifying a Carotenoid Cleavage Dioxygenase (CCD4) Gene Controlling Yellow/White Fruit Flesh Color of “Piqiutao” (White Fruit Flesh) and Its Mutant (Yellow Fruit Flesh)

Abstract: To better understand the fruit flesh coloration mechanism of peach (Prunus persica), the composition and accumulation of carotenoids were compared, the expression profile of key genes involved in carotenoid biosynthetic and catabolic pathways was performed, and the differentially expressed genes were identified using "Piqiutao" (white fruit flesh) and its mutant yellow "Piqiutao" at different fruit development stages. The results showed that the total carotenoid content in yellow "Piqiutao" was remarkably high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Carotenoids are cleaved by carotenoid cleavage dioxygenases (CCDs), and these enzymes are generically divided into five subfamilies: NCED (nine-cis-epoxycarotenoid dioxygenase), CCD1, CCD4, CCD7, and CCD8 [ 47 ]. A large number of studies have reported that the differential expression of CCD1s and CCD4s results in differences in carotenoid content in various plant species and cultivars, such as the different colored fruits of peach ( PpCCD4 [ 8 , 48 ]) and summer squash ( CpCCD4a and CpCCD4b [ 49 ]) and the different colored flowers of chrysanthemum ( CmCCD4a [ 9 ]), osmanthus ( OfCCD4 [ 10 ]), oncidium ( OgCCD1 [ 50 ]), and daffodil ( NpCCD4 [ 51 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Carotenoids are cleaved by carotenoid cleavage dioxygenases (CCDs), and these enzymes are generically divided into five subfamilies: NCED (nine-cis-epoxycarotenoid dioxygenase), CCD1, CCD4, CCD7, and CCD8 [ 47 ]. A large number of studies have reported that the differential expression of CCD1s and CCD4s results in differences in carotenoid content in various plant species and cultivars, such as the different colored fruits of peach ( PpCCD4 [ 8 , 48 ]) and summer squash ( CpCCD4a and CpCCD4b [ 49 ]) and the different colored flowers of chrysanthemum ( CmCCD4a [ 9 ]), osmanthus ( OfCCD4 [ 10 ]), oncidium ( OgCCD1 [ 50 ]), and daffodil ( NpCCD4 [ 51 ]).…”
Section: Discussionmentioning
confidence: 99%
“…revealed the differences in the expression patterns of the CCD4 gene between the white-fleshed ‘Piqiutao’ and its yellow-fleshed mutant. The yellow-fleshed peach mutant had a significantly lower expression level of CCD4 than white-fleshed ‘Piqiutao’, resulting in its yellow flesh phenotype ( Wen et al., 2020 ). In this study, the transcriptome analysis of BF1 and HF1 revealed that CCD8 is probably the gene in the CCD family that affects the flesh color of the F 1 hybrid generation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, CCD4-catalyzed degradation of carotenoids affects the color of fruit flesh and flower. Several studies have demonstrated that inactivation or decreasing the expression of CCD4 could result in the accumulation of carotenoids in peach flesh ( Brandi et al., 2011 ; Adami et al., 2013 ; Falchi et al., 2013 ; Ma et al., 2014 ; Bai et al., 2016 ; Wen et al., 2020 ). NCED has been isolated from a variety of species, and it lower expression level can impede the breakdown of carotenoids, leading to changes in plant color ( Rodrigo et al., 2006 ; Jiang et al., 2019 ; Lana et al., 2020 ; Yungyuen et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…CCD4 in flowering plants is mainly active in chromoplasts, where it determines coloration in petals and fruits by degrading carotenoid pigments. Knockout mutants of CCD4 in ipomea, chrysanthemum, and brassica caused white petals to turn pale-yellow/yellow, and in peach, they caused a change from white to yellow-fleshed fruits ( Adami et al, 2013 ; Ma et al, 2014 ; Zhang et al, 2015 ; Jo et al, 2016 ; Watanabe et al, 2018 ; Wen et al, 2020 ). In Arabidopsis, ccd4 and ccd1 mutants increased seed carotenoid levels, mainly in lutein, neoxanthin, and violaxanthin, with a more pronounced effect in ccd1 mutants ( Gonzalez-Jorge et al, 2013 ).…”
Section: Carotenoid Biosynthesis – the Central Pathwaymentioning
confidence: 99%